Adjustment costs of monetary integration in CARICOM. - BENNETT, Karl M. (1994)
Attempts to ascertain the potential effectiveness of monetary policy and exchange rate adjustment as instruments of short-run stabilisation, with special reference to Barbados, Guyana, Jamaica, and Trinidad and Tobago.